THE ROLE OF INNOVATION AND TECHNOLOGY IN DETERMINING THE SPECIALIZATION OF AGRICULTURAL ENTERPRISES - ORISHCHENKO, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Ensuring the dynamic development of agriculture in modern conditions is associated with introducing innovations in this area. Innovations are aimed at increasing productivity in the agricultural sector of the economy based on the renewal of technical, technological, and organizational bases of production and play a key role in expanding the production of competitive products. Innovative activity in agriculture has significant features compared to other sectors of the economy. It is determined by the influence of natural and climatic conditions, the biological basis of production, and the seasonality of agricultural activity. Due to the multi-sectoral structure of agricultural production, a wide range of innovations can be classified according to various criteria. In addition, the agricultural sector is characterized by a unique, innovative infrastructure, which includes various organizational forms aimed at developing scientific and technological progress, increasing the intensity of production, and, ultimately, increasing efficiency. Innovative development of agriculture also creates favorable opportunities for addressing issues of sustainable development related to agricultural activities, primarily the protection and efficient use of land and water resources. In this regard, the widespread use of agricultural innovations will contribute to global food security. Specialization leads to an improvement in the structure of agricultural production, a constant increase in the incomes of producers and workers, and a positive effect on the reliable satisfaction of the population's needs for important agricultural products — innovative development results in increased yields, improved product quality, and increased sales volumes. At the same time, the cost of production is reduced, production processes are optimized, and capital equipment and labor productivity are increased, which positively affects economic activity's profitability. The introduction of innovations increases the competitiveness of agricultural products in the domestic and foreign markets, which contributes to improving the financial and economic indicators of agricultural enterprises.
Keywords: industry; structure; production; innovation; technology; development